Leading Pharmaceutical Innovation Trends and Drivers for Growth in the Pharmaceutical Industry - Gassmann, Oliver. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Pharmaceutical giants have doubled their investments in drug development in the past decade only to see new drug approvals remain constant. This book investigates and highlights a set of proactive strategies aimed at generating sustainable competitive advantage based on value-generating business practices. We focus on three sources of pharmaceutical innovation: new management methods in the drug development pipeline, new technologies as enablers for cutting-edge R&D, and new forms of cooperation and internationalization, such as open innovation in the early phases of R&D. Our findings are illustrated by cases from Europe, the US, and Asia. "One way we try to foster innovation - both the technological innovation and the organizational innovation - is to align our business objectives with our ideals." Dr. Daniel Vasella, CEO, Novartis International "Pharmaceutical innovation is in crisis. The industry will have to change both its innovation processes and its business models in order to reverse these trends and prosper in the future. Professors Gassmann, Reepmeyer and von Zedtwitz have marshalled together an impressive array of research in one volume. This book should prove to be an indispensable resource for all participants in the pharmaceutical industry." Prof. Henry Chesbrough, Executive Director, Center for Open Innovation, Haas School of Business, University of California, Berkeley "It´s time for a paradigm shift in pharmaceutical R&D. This book will tell you why." Dr. Goetz Baumann, Business Unit Manager, Hoffmann-La Roche (Germany) "This book offers a fact based, comprehensive insight to the increasing challenges of today`s drug development. Well worth reading not just for newcomers to the industry but also for industry professionals who want to understand the big picture". Dr. Pius Renner, Head of Strategic Planning and Portfolio Management in Development, Novartis Pharma .